Professional Skills Requirements for Accountants: Analysis of Accounting Job Advertisements - Ghani, Mohammad Abdul; Suryani, Ani Wilujeng (Universitas Pendidikan Indonesia, 2020)
This study provides a new insight to the accounting literature by investigating the most required skills for accountants through the analysis of job advertisements. This study obtained 523 job advertisements from an online job seeker website in accounting including financial accountants, auditors, and tax accountants. By using content analysis, the results of the study show that interpersonal and communication skills are considered to be the most important skills for accountants, especially in Indonesia. In addition, the findings show the importance of foreign language skills in obtaining a job. However, based on the comparison with similar studies in Australia and New Zealand, technical skills are ranked more important in Indonesia. This study implies that accounting education should stress more on the softskills rather than technical skills to generate work-ready accountants.